Cross-Cultural Care Training for Pediatric Hematology/Oncology Fellows - Amulya Nageswara Rao; Deepti Warad; Vilmarie Rodriguez (Association of American Medical Colleges, 2017)
Introduction Physicians are entrusted with the medical care of culturally and socially diverse patient populations. In addition, pediatric hematologists/oncologists are faced with the challenge of taking care of children with life-threatening and complex conditions. We implemented a cross-cultural care training curriculum for our pediatric hematology/oncology fellows with the goal of preparing them to handle complex clinical situations while navigating different social and cultural belief systems. Methods The curriculum includes a precourse self-reflection; a learning module with a review of published literature; faculty-facilitated small-group role-play simulations; interactive sessions with language interpreters and physicians from different cultural, ethnic, and religious belief systems; and a postcourse reflection. Results Fellows who participated in the curriculum strongly agreed that the module was helpful, indicating that it enhanced their communication skills, improved delivery of cross-cultural care, and had a sustained impact on their interaction with medical language interpreters. Discussion Cross-cultural care training should be integrated into any pediatric hematology/oncology training curriculum. Sessions directed at addressing the perceived gaps between physician awareness and the patient's belief systems can increase awareness of personal biases in practice and improve interview techniques. Likewise, self-reflection can help physicians apply their medical knowledge and skills in the appropriate cultural and social context, thereby improving patient satisfaction, partnerships, and health care outcomes.